Occlusal characteristics and orthodontic treatment need in black adolescents in Salvador/BA (Brazil): an epidemiologic study using the Dental Aesthetics Index - Arthur Costa Rodrigues Farias; Maria Cristina Teixeira Cangussu; Rogério Frederico Alves Ferreira; Marcelo de Castellucci (Dental Press Journal of Orthodontics, 2013)
OBJECTIVE: The objective of this article is to evaluate the need of orthodontic treatment, prevalence and severity of the malocclusions in individuals of black ethnicity in a representative sample of schoolchildren of the city of Salvador/Brazil, as well as to verify if the malocclusion was affected by socio-demographic conditions such as age and gender. METHODS: The reference population was constituted of schoolchildren with age between 12 and 15 years, enrolled in public and private schools. The malocclusion was evaluated in 486 students of black ethnicity, with ages varying from 12 to 15 years, selected in random sample in multiple stages. The adopted significance level was 1% and the power of the test was 90%. A questionnaire registering demographic characteristics was filled out by each individual. The Dental Aesthetics Index (DAI) was used by previously calibrated examiners (kappa 0.89), according to criteria of the World Health Organization. RESULTS: It was verified that most of the individuals (76%) had little or any need for orthodontic treatment. About 24% showed a condition of severe malocclusion, culminating in a vital need for orthodontic treatment. The main occlusal characteristics found in the group with high need of orthodontic treatment were dental crowding and accentuated overjet. The age was positively related to the improvement of the maxillary overjet and to the presence of crowding. CONCLUSION: The development of public politics that aim the insertion of orthodontic treatment among the procedures of health programs, with the implementation and development of specialized centers, is fundamental. OBJETIVO: averiguar a necessidade de tratamento ortodôntico, prevalência e severidade das más oclusões em indivíduos negros numa amostra representativa de escolares da cidade de Salvador/BA (Brasil), além de determinar se as más oclusões eram afetadas por condições sociodemográficas como idade e sexo. MÉTODOS: o desenho epidemiológico foi transversal, e a população de referência se constituiu de escolares com idades entre 12 e 15 anos, matriculados em escolas de primeiro e segundo graus, públicas e privadas. Participou do estudo um total de 486 indivíduos sorteados em amostra probabilística em múltiplo estágio. O nível de significância adotado foi de 1% e o poder do teste foi de 90%. Aos participantes foram aplicados questionários registrando características demográficas e, depois, avaliados por examinadores previamente calibrados (Kappa 0,89), utilizando-se o Índice de Estética Dentária (IED) segundo critérios da Organização Mundial de Saúde. RESULTADOS: constatou-se que a maioria dos indivíduos (76%) observados nesse estudo possuía pouca ou nenhuma necessidade de tratamento ortodôntico. Cerca de 24% apresentaram uma condição de má oclusão severa, acarretando uma imprescindível necessidade de tratamento ortodôntico. As principais características oclusais encontradas no grupo com maior necessidade de tratamento ortodôntico foram apinhamento dentário e overjet maxilar acentuado. A idade foi positivamente relacionada com a melhora do quadro do overjet maxilar e com a presença de apinhamento dentário. CONCLUSÃO: torna-se fundamental o desenvolvimento de políticas públicas que objetivem a inserção do tratamento ortodôntico entre os procedimentos dos programas de saúde, com a implementação e desenvolvimento de centros especializados.